Vector Transmission Alone Fails to Explain the Potato Yellow Vein Virus Epidemic among Potato Crops in Colombia - Cuadros, Diego F.; Hernandez, Anngie; Torres, Maria F.; Torres, Diana M.; Branscum, Adam J.; Rincon, Diego F. (Frontiers in Plant Science, 2017)
The potato yellow vein disease, caused by the potato yellow vein virus (PYVV), is a limiting potato disease in northern South America. The virus can be transmitted either by the greenhouse whitefly (GWF), Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae), or through vegetative propagules, such as infected tubers. Recently, GWF populations have been spotlighted as one of the main drivers of PYVV re-emergence, and consequently, PYVV management has been predominantly directed towards vector control, which is heavily based on insecticide use. However, the drivers of the PYVV outbreaks as well as the contribution of GWF populations on the spread of PYVV among potato crops are still not completely understood. This study aims to assess the role of the GWF as a driver of the PYVV epidemic in the potato-producing areas in Colombia, one of the countries more severely affected by the PYVV epidemic, and whose geography allows the study of the spatial association between the vector and the disease epidemic across a wide altitude range. The geographical clusters where the PYVV epidemic is concentrated, as well as those of farms affected by the GWF were identified using a novel spatial epidemiology approach. The influence of altitude range on the association between PYVV and T. vaporarioum was also assessed. We found a relatively poor spatial association between PYVV epidemic and the presence of the GWF, especially at altitudes above 3,000 meters above mean sea level. Furthermore, GWF populations could only explain a small fraction of the extent of the PYVV epidemic in Colombia. Movement of infected seed tubers might be the main mechanism of dispersion, and could be a key driver for the PYVV infection among potato crops. Agricultural policies focused on improving quality of seed tubers and their appropriate distribution could be the most efficient control intervention against PYVV dispersion.